2017
DOI: 10.1073/pnas.1619433114
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to action potential depression of a rat axon terminal in vivo

Abstract: The shape of the presynaptic action potential (AP) has a strong impact on neurotransmitter release. Because of the small size of most terminals in the central nervous system, little is known about the regulation of their AP shape during natural firing patterns in vivo. The calyx of Held is a giant axosomatic terminal in the auditory brainstem, whose biophysical properties have been well studied in slices. Here, we made whole-cell recordings from calyceal terminals in newborn rat pups. The calyx showed a charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 56 publications
0
47
1
Order By: Relevance
“…Na + flows into the cytosol during the firing of action potentials, while the location of Na + channels in the calyx of Held is under debate (Huang and Trussell, 2008; Kim et al, 2010; Leao et al, 2005; Sierksma and Borst, 2017). Whole-cell recordings were made at the mouse calyx of Held and the presynaptic Na + changes during action potential (AP) firing were assayed using two-photon laser scanning microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Na + flows into the cytosol during the firing of action potentials, while the location of Na + channels in the calyx of Held is under debate (Huang and Trussell, 2008; Kim et al, 2010; Leao et al, 2005; Sierksma and Borst, 2017). Whole-cell recordings were made at the mouse calyx of Held and the presynaptic Na + changes during action potential (AP) firing were assayed using two-photon laser scanning microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In P12–P14 rat brain slices, reliable synaptic transmission was generally possible at frequencies up to 600 Hz for 50 stimuli (Taschenberger and von Gersdorff, 2000). In vivo recordings from mice showed that AP showed little or no (<4%) depression when instantaneous firing frequencies over 200 Hz (Sierksma and Borst, 2017). Here we showed amplitude decrease during 100 Hz firing for 4 s was 3% while 333 Hz firing decreased the AP amplitude by 20% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2), indicating very stable AP waveforms during prolonged high-frequency firing. Two factors appeared to be crucially important for the lack of a change in the AP’s shape: fast recovery of Na + channels from AP depression (Leao et al, 2005) and relative stable while negative membrane potential following the AP (Sierksma and Borst, 2017). The recovery of Na + from inactivation is sharply dependent on the membrane potential, as 20 mV of hyperpolarization double the speed of recovery (Leao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This switch may be explained by an increase in the currents 333 over the calyceal membrane facing the synaptic cleft or by an increase in the coupling between the 334 pre-and the postsynaptic membranes. The currents depend on apposition area (Hoffpauir et al, 335 2006;Holcomb et al, 2013), time course of the calyceal AP, which accelerates considerably during 336 early development (Taschenberger & von Gersdorff, 2000;Sierksma & Borst, 2017), isochronicity of 337 the presynaptic currents, and the subcellular distribution of presynaptic ion channels. In addition, 338 the coupling depends on synaptic cleft resistivity and postsynaptic admittance (Savtchenko, 2007).…”
Section: Strong Inputs and Prespikes 308mentioning
confidence: 99%